Factors associated with the unwillingness of Jordanians, Palestinians and Syrians to be vaccinated against COVID-19 - Zein, Sima; Abdallah, Sarah B.; Al-Smadi, Ahmed; Gammoh, Omar; Al-Awaida, Wajdy J.; Al-Zein, Hanan J. (PLOS Neglected Tropical Diseases, 2021)
Author summary This study investigated vaccine willingness, unwillingness, or hesitancy by assessing the intention to get vaccinated against COVID-19. We found that a considerable percentage of participants are unwilling/hesitant to receive the COVID-19 vaccine. Perceived barriers to vaccination, namely the lack of rigorous evaluation of the vaccines and the possible long-term health risks associated with it, were significant predictors of COVID-19 vaccination intent. A substantial proportion of participants willing to get vaccinated were the 18–35 years old and the participants with a high school diploma or less.